Contesting the Origins of the First World War: An Historiographical Argument - Paddock, Troy R. E. (Routledge studies in modern history, 2020)
Keywords: Causes; Historiography; Historiography; World War, 1914-1918; World War, 1914-1918; dept.his; faculty_collection

The russian holy synod and the greeks: Reconsidering greek-russian relations in the early modern period (16th–18th centuries) - Chrissidis, Nikolaos A. (Canadian-American Slavic Studies, 2020)
The article first surveys Greek interpretations of the creation of the Russian Holy Synod by Peter the Great. It provides a critical assessment of the historiographical paradigm offered by N.F. Kapterev for the analysis of Greek-Russian relations in the early modern period. Finally, it proposes that scholars should focus on a Greek history of Greek-Russian relations as a complement and possibly corrective to the Kapterev paradigm. © verlag ferdinand schöningh, 2020.
Keywords: Aleksander stourdza; Greek-russian relations; Konstantin oinonomos; Nikolai kapterev; Peter the great; Russian holy synod; dept.his; peer-reviewed